If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -13 = -5x + -2 Reorder the terms: -13 + 6x = -5x + -2 Reorder the terms: -13 + 6x = -2 + -5x Solving -13 + 6x = -2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -13 + 6x + 5x = -2 + -5x + 5x Combine like terms: 6x + 5x = 11x -13 + 11x = -2 + -5x + 5x Combine like terms: -5x + 5x = 0 -13 + 11x = -2 + 0 -13 + 11x = -2 Add '13' to each side of the equation. -13 + 13 + 11x = -2 + 13 Combine like terms: -13 + 13 = 0 0 + 11x = -2 + 13 11x = -2 + 13 Combine like terms: -2 + 13 = 11 11x = 11 Divide each side by '11'. x = 1 Simplifying x = 1
| 16w-3w-10w-3w+-4w=20 | | 16w-3w-10w-3w+-4w=10 | | 3N=123 | | 6v-3v+5v-7=9 | | 18y=6x-18 | | -2-6y=6 | | 8b-8b+2b=12 | | -3(5t-3)+5t=6t-4 | | y(5-y)-(5*y-y*2)= | | 8x-(2x+7)=41 | | -40x=10 | | 6x-9=6(x+2) | | 4+3y=6 | | -3u+5u=18 | | -20j+19j=-16 | | 2x-2x+4x-1=15 | | 6h+5h-3h=8 | | 4t-6t+19t+-11t=-12 | | 2u-2u+3u+4u-3u=20 | | 24x+12-24x-36=4x | | 4a=(4k-sk)2 | | 10t^2-33t-7=0 | | -16a-12a+20a=-16 | | 3(3y+8)-4= | | 22=2L+12 | | -x=5y-12 | | 4a=ak-tk | | 11k+4k-11k-k=9 | | 10p-4p+2p-p-6p=19 | | 4x+9(0)=36 | | 16b-9b=14 | | 4(0)+9y=36 |